Justificación Económica Para La Implementación De Un Dispositivo De Disipación De Energía Estructural (2024)
The main objective of this graduate work is to analyze the economic feasibility of incorporating seismic isolators in buildings located in Cucuta, Colombia. Considering its impact on the structural resilience to seismic events. The methodology included a cost comparison between a structure with an isolated base and a structure with a conventional fixed base previously designed under the Nsr-10 guidelines. In addition, an evaluation and comparison of structural parameters and performance of both structures was performed.